UTICAJ PLIOMETRIJSKOG TRENINGA NA EKSPLOZIVNU SNAGU OPRUŽAČA NOGU - Aleksandar Kukrić; Borko Petrović; Radenko Dobraš; Bojan Guzina (University of Banja Luka, Faculty of physical education and sport, 2010)
In the period of ten weeks junior basketball players divided into two experimental and controlgroups, were subjected to various training programs. Patients in experimental group, in addition toregular basketball training, additional trained plyometric model of training twice a week, whilerespondents in the control group had only a technical-tactical basketball training. The aim of thisstudy was to test the impact of content plyometric training on explosive leg strength exstensors inperforming various jumps in junior basketball players. Tested were two jumps: Countermovementjump and Squat jump, and observed the following variables: maximum jump height (h), maximumforce in concentric contraction (Fmax) and time implementation maximum force in concentriccontraction (tmax). Comparing the results obtained on the basis of initial and final measurementsunambiguously proved that the tested variables are changed under the influence of experimentalfactors. In two tested jump significantly improve the maximum jump height (p=.00) and maximumforce (p=.00). Time implementation maximum force is not changed significantly during the tenweeks treatment. Research has proven that plyometric training methods affect the development ofexplosive strength of legs extensors of basketball junior players.